Landing differences between men and women in a maximal vertical jump aptitude test - Abian, J.; Alegre, L. M.; Lara, A. J.; Rubio, J. A.; Aguado, X. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. The aim of this study was to analyze the gender differences in the vertical ground reaction forces and the position of the center of gravity during the landing phase of a maximal vertical jump aptitude test. Methods. The push-off, flight and landing phases of the jumps of 291 males (age=19.6±2.8 years) and 92 females (age=19.2±2.6 years), applicants to a Spanish faculty of sports sciences, were analyzed with a force platform. Results. The greatest differences between men and women were found in the jump performance (women=25.6±3.5 cm; men=35.5±4.5 cm) and second peak vertical force value of the landing phase (women=5.89±2.06 times body weight; men=7.51 ±2.38 times body weight), the values being greater in the men's group (P<0.001). Correlation coefficients showed that the women utilized a different landing pattern than the one utilized by the men. Conclusion. Contrary to the authors' expectations, women showed lower second peak vertical force values during the landing. Taking into account only a kinetic point of view, they would have a lower risk of injury during the landing movement of maximal jumps. The lower values in the peak force, the delay of the impact of the calcaneus and the longer path of the center of gravity during the landing phase found in the women's group were related to a landing technique that is different from that of men.